2022
DOI: 10.1371/journal.pone.0271567
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to perform first aid among high school students and associated factors in Hue, Vietnam

Abstract: Background Adolescents who are willing to perform first aid can help prevent injuries and ultimately death among themselves and others involved in accidents or injuries. This study aims to estimate the prevalence of students’ willingness to perform first aid procedures and additionally examine associated factors among high school students in Hue, Vietnam. Methods A cross-sectional study utilizing multi-stage stratified random sampling was conducted between April to July 2020 by investigating 798 high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similarly, in the study [29] with nursing faculty students in China, the self-efficacy of those who had the first-aid training was higher. In the study [30] with high school students in Vietnam, it was found that 46% of the students who had the first-aid training and only 26% of those who did not have training had high first-aid self-efficacy. The study [30] also investigates the participants' barriers to practicing the first-aid.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, in the study [29] with nursing faculty students in China, the self-efficacy of those who had the first-aid training was higher. In the study [30] with high school students in Vietnam, it was found that 46% of the students who had the first-aid training and only 26% of those who did not have training had high first-aid self-efficacy. The study [30] also investigates the participants' barriers to practicing the first-aid.…”
Section: Discussionmentioning
confidence: 98%
“…In the study [30] with high school students in Vietnam, it was found that 46% of the students who had the first-aid training and only 26% of those who did not have training had high first-aid self-efficacy. The study [30] also investigates the participants' barriers to practicing the first-aid. The first barrier is fear of making a mistake during the first-aid/damaging the injured person, and the second barrier is lack of the first-aid training [30].…”
Section: Discussionmentioning
confidence: 98%
“…Educating children in school helps them not only know how to handle an accident, but also how to handle crises, as accidents and unpleasant events occur frequently in the family and school environment [ 35 ]. To sum up, we firmly feel that teaching young children both resuscitative and non-resuscitative first aid is essential [ 34 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Lack of confidence with first aid and related fear of making mistakes are well-known as predominant factors impeding willingness of laypeople to intervene in a health emergency. 4,5 To overcome these barriers in real-life critical situations, people may turn online to look for advice on how to give help.…”
Section: Introductionmentioning
confidence: 99%